The Impact of Strategic Management on Organizational Performance: An Empirical Study - Usmany, Paul; Anna M. Ngabalin; Utami, Try Wahyu; Jasmin; Putrianti, Flora Grace (International Journal of Economics (IJEC), 2024)
In today's era of globalization and intensifying market competition, business leaders, particularly in the food and beverage (F&B) industry, are compelled to pursue continuous innovation and implement effective strategic management practices to remain competitive and succeed in an increasingly complex market. In this study, we will delve deeply into the implementation of strategic management in an F&B enterprise, namely Ayam Guling Mister (AGM). It is the aim of this research to provide readers with an understanding of the concepts and basic principles of strategic management and their applicability to the F&B industry. Furthermore, the factors influencing the successful implementation of strategic management will be discussed. This research employs a qualitative approach, which is particularly suited to the investigation of the application of strategic management in the context of food and beverages production. This enables the perspectives of organisational leaders on the management of strategic initiatives to be elucidated, thereby facilitating an understanding of the processes involved in maintaining the viability of a product. The findings from this research indicate that the implementation of strategic management at AGM is crucial to ensure business success and sustainable growth.